RESPON PERKECAMBAHAN BENIH SENGON LAUT (Paraserianthes falcataria (L.) Nielsen) TERHADAP ALELOPATI DAUN DAN RHIZOME ALANG-ALANG (Imperata cylindrica L.) - Pangemanan, Euis F.S.; Ratag, Semuel P. (Universitas Sam Ratulangi, 2017)
ABSTRACT A plant species can release a toxic compound which can inhibit the growthof other plant species. The success of planting certain tree species, both inside and outside the forest area with agroforestry system can be affected by allelopathy of other plant species. The objective of this research was to study the response of sengon laut (Paraserianthes falcataria (L.) Nielsen) seed germination on cogongrass (Imperata cylindrica L.) leaves and rhizomes allelopathy. The experimental design was a randomized complete design with four replicates. The treatments were leaves and rhizomes extracts of cogongrass, and water as control. The results showed that the extract concentration of 20 % (weight/volume), then the sengon laut seed germination was not affected by the extracts. Keywords: sengon laut, cogongrass, allelopathy, seed germination